Barriers and facilitators to global access to life-saving skills training: an international cross-sectional survey - Marcus Eng Hock Ong; Freddy Lippert; Lin Zhang; Willem Stassen; So Yeon Joyce Kong; Audrey L Blewer; Yeh Lai Chern; Andrew Fu Wah Ho (BMJ Open)
Introduction Emergency care begins in the community, who are often the first on the scene. Where emergency care systems are nascent or absent, bystanders represent the only prehospital emergency care that victims might receive. It is important to equip bystanders through life-saving skills training (LST). The aim of this study was to describe access to LST for laypersons globally and to determine barriers or facilitators for access to LST globally.Methods A global cross-sectional, online survey was undertaken with stakeholders involved in LST programmes and policies through purposive, snowball sampling. The invitation for participation was distributed to local, regional and international emergency care and resuscitation organisations and their membership. Data were collected using a custom-designed survey, based on the literature and following pilot testing. Data were analysed descriptively and visualised according to countries and regions. Logistic regression was used to identify variables predictive of LST.Results A total of 302 responses from 67 countries were analysed. Majority of responses were from high- or upper-middle income countries (61.2%) compared with low- or lower-middle income countries (38.8%). All respondents from Europe reported reliable access to LST. Of respondents who reported no LST is delivered, the highest proportion of these represented the Eastern Mediterranean (18.2%), Africa (17.1%) and South America (16.9%). The most common barrier to accessing LST were cultural views surrounding LST (69.2%), while the most common facilitator was interpersonal relationships to encourage the uptake of LST (71.9%). Country level of income (adjusted OR (AOR) 4.31 (95% CI 1.62 to 11.45), p<01), urban location (AOR 10.57 (95% CI 3.32 to 33.66), p<0.001) and level of EMS development (OR 5.73 (95% CI 1.47 to 22.30), p=0.01) were predictive of access to LST.Conclusion This study highlights considerable inequity in LST access globally. Future work should seek to mitigate barriers and leverage facilitators through participatory and community-oriented approaches to LST.